PENETAPAN HARGA POKOK PRODUKSI PAKAIAN SERAGAM AKADEMI KEBIDANAN PERMATA HUSADA SAMARINDA PADA PENJAHIT SARTIKA EXPRESS SAMARINDA - Supriyatno, Andik (EKONOMIA, 2012)
Andik Supriyatno. The pricing of goods manufactured uniforms Midwifery Academy Husada Samarinda Jewel Express Tailors Sartika Samarinda (under the guidance of the mother and father of titin Ruliana and Imam Nazaruddin Latif). The purpose and this paper is to calculate the cost of goods manufactured uniforms Midwifery Academy Samarinda Jewel Husada full costing method in Tailor Sartika Express Samarinda. In accordance with the purpose of writing this, the principal issues raised: Is the determination of cost of goods manufactured uniforms Midwifery Academy Husada Samarinda Jewel Express Tailors Sartika higher than the base price set by the author using the full costing method in July 2011''? Based on these fundamental issues, the proposed hypothesis as follows: "Suspected Determining the cost of production Midwifery Academy uniforms Husada Samarinda Jewel Express Tailors Sartika lower than the cost of production is determined by the authors using the full costing". The analytical tool used in this study is the determination of the cost of production using full costing method and compare the cost of production by Tailor Sartika Express Samarinda production costs according to the analysis.